ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI LITERASI KEUANGAN MIKRO SYARIAH - Nur Wahyuni (JASIE, 2022)
This study aims to examine the effect of Islamic microfinance literacy. The method used in this study is a quantitative method using the SPSS 16 application. The scope of this research is the general public. income, age and education level partially have a significant positive effect on Islamic microfinance literacy. This is evidenced by the Anova F test with a calculated F value of 10,860 and an F table of 2.47, while the significant probability value in this study is 0.000 <0.05, it can be concluded that Ho is rejected and Ha is accepted. Based on the hypothesis testing of influential income, this is evidenced by the t test, it is found that the calculated value of income is 4.500 greater than t table 0.1661 and the significance value is 0.000 less than 0.05. Then the hypothesis is accepted. The age variable has a t-count value greater than t-table, namely 2.477>0.05, meaning that age has a significant effect. While the variable income level t arithmetic value is smaller than the value of t table that is 0.631 <1.661, the education variable has no effect on financial literacy. So, the conclusion that can be drawn is that income and age have a significant positive effect, while the level of education has no effect on Islamic microfinance literacy.Keywords: financial literacy, income, age, education level